Mediation in the asia-pacific region : transforming conflicts and building peace - Bagshaw, Dale.; Porter, Elisabeth ([S.l.] : Routledge, 2009)
This book examines mediation in connection with peacebuilding in the Asia-Pacific region, providing practical examples which either highlight the weaknesses within certain mediation approaches or demonstrate best-practice. The authors explore the extent to which current ideas and practices of mediation in the Asia-Pacific region are dominated by Western understandings and critically challenge the appropriateness of such thinking. Featuring a range of case studies on Fiji, Vanuatu, Papua New Guinea, Malaysia, Vietnam, China, Singapore, Indonesia, the Philippines and Thailand, this book has three main aims: To challenge dominant Western practices and ways of thinking on mediation that currently are being imposed in the Asia-Pacific region; To develop culturally-fluent and socially just mediation alternatives that build upon local, traditional or religious approaches; To situate mediation within ideas and practices on peacebuilding. Making a unique contribution to peace and conflict studies literature by explicitly linking mediation and peacebuilding practices, this book is a vital text for students and scholars in these fields.
Keywords: Asia; Conflict management; Mediation; Mediation, International; Pacific Area; Peace-building; Political science